Transnational society as a mirror of international society: a reinterpretation of contemporary world order. Issue 3 (November 2019) - Davies, Thomas
Abstract: Although there has been widespread attention to the apparent rise of a transnational society of cross-border non-state actors alongside the international society of states, transnational society and international society have traditionally been treated as distinctive domains with different institutions. This article, by contrast, aims to transform theorization of world order through its investigation of how actors in transnational society have developed institutions that mirror in notable respects some of the primary institutions of the international society of states such as through serving constitutive and regulative functions. In addition to delineating these institutions of transnational society, the article interrogates the interdependence of these institutions of transnational society and those of international society, as well as their differences and repercussions for world order. The analysis considers how, in conjunction with the contribution of institutions of international society to international order, institutions of transnational society contribute to transnational order. By exploring not only the tensions between but also the complementarities of transnational and interstate institutions, the article both provides a reinterpretation of contemporary world order and helps reveal the potential for its more harmonious operation.